2008
DOI: 10.1074/mcp.m700321-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Snake Venoms Using Soluble Polymer-based Isotope Labeling

Abstract: We present the design and synthesis of a new quantitative strategy termed soluble polymer-based isotope labeling (SoPIL) and its application as a novel and inclusive method for the identification and relative quantification of individual proteins in complex snake venoms. The SoPIL reagent selectively captures and isolates cysteine-containing peptides, and the subsequent tagged peptides are released and analyzed using nanoflow liquid chromatography-tandem mass spectrometry. The SoPIL strategy was used to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Click Labeling and Affinity Enrichment. Procedures by Speers et al and Galan et al 20,21 were modified for click labeling of the enrichment reagent. Briefly, the peptide mixture produced from the in-solution digestion was reduced to dryness and reconstituted in PBS buffer (100 mM sodium phosphate, 0.15 M NaCl, pH 7.5) that was supplemented with 1 µL of 100 mM Tris-[1-benzyl-1H-1,2,3-triazol-4-yl)methylamine (TTA) (0.25 mM final concentration), 20 µL of 50 mM CuSO 4 (2.5 mM final concentration), and 40 µL of 50 mM Tris (2-carboxyethyl) phosphine (5 mM final concentration) to a final volume of 400 µL.…”
Section: Methodsmentioning
confidence: 99%
“…Click Labeling and Affinity Enrichment. Procedures by Speers et al and Galan et al 20,21 were modified for click labeling of the enrichment reagent. Briefly, the peptide mixture produced from the in-solution digestion was reduced to dryness and reconstituted in PBS buffer (100 mM sodium phosphate, 0.15 M NaCl, pH 7.5) that was supplemented with 1 µL of 100 mM Tris-[1-benzyl-1H-1,2,3-triazol-4-yl)methylamine (TTA) (0.25 mM final concentration), 20 µL of 50 mM CuSO 4 (2.5 mM final concentration), and 40 µL of 50 mM Tris (2-carboxyethyl) phosphine (5 mM final concentration) to a final volume of 400 µL.…”
Section: Methodsmentioning
confidence: 99%
“…SoPIL was applied to the quantitative analysis of snake venoms (see Section IV.B) (Galan et al, 2008). Guttman and co-workers recently reported the fluorescent isotope-coded affinity tag (FCAT) (Rivera-Monroy, Bonn, & Guttman, 2008).…”
Section: Combined Quantitative Methodsmentioning
confidence: 99%
“…In addition, a better understanding of geographical and environmental variations in venoms is essential to the development of agents to treat snakebites. Using the SoPIL strategy, Galan and co-workers performed a quantitative analysis of venoms from two pairs of snakes: two Mohave rattlesnakes (types A and B) and two from geographically unrelated snakes (Southern Pacific rattlesnake and Mapanare snake) (Galan et al, 2008). The authors highlighted differences in cysteinerich proteins that revealed intraspecies and geographicalenvironmental variations.…”
Section: B Cysteine-rich Proteins and Peptidesmentioning
confidence: 99%
“…These peptide-centric approaches are mainly used to quantify relative differences in peak intensity of the same analyte between multiple samples. Applications to venomics has been so far scarce, including the relative quantification of type A and type B venoms from the same species of C. s. scutulatus and the venoms from two geographically unrelated snakes from North and South America, C. o. helleri and B. colombiensis , respectively [ 25 ]. More recently, the comparative analyses of venom during the neonate-to-adult transition of Bothrops jararaca [ 26 ] and Gloydius brevicaudus were carried out [ 27 ].…”
Section: Peptide-centric Mass Spectrometry-based Relative Quantificatmentioning
confidence: 99%